Casos y cosas: semanario popular (Vol. 1, No. 37) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: En hierro frío, solteros a casarse!, Loreto pueblo infelíz...., La cintura, Falta de humanidad, Escuela fiscal de baile?, La moral de una autoridad, Escena prehistórica, El pecado eterno

ENGLISH: In cold iron, bachelors to marry, Loreto village infelíz...., waist, lack of humanity, fiscal school of dance?, the morality of an authority, prehistoric esceas, eternal sin
Cases and things: popular weekly (Vol. 1, No. 37)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas